Growth and Yield of Tomato (Lycopersicum esculentum Mill.) Due to Application of Hormonic PGR and NPK Fertilizer - Anis Nurmala Puspitasari; Didik Utomo Pribadi; Hadi Suhardjono (The University of Lampung, 2023)
Tomatoes have high economic value with community demands increases every year. However, the productivity of tomatoes farmers in Indonesia can not meet the demands of Indonesian consumers. Efforts to solve low productivity in tomatoes cultivation can be made through certains cultivation techniques. The intention of this study is to acquire appropriate combination of “Hormonik” Plant Growth Regulator (PGR) concentrations and NPK fertilizer dosages for the optimum growth and yield of tomato plants. This study used a factorial experimental method with a completely randomized design (CRD). The first factor is Hormonik PGR concentrations (H) in 4 different treatment levels that consist of control variable (no PGR added) (H0), 6 ml/l (H1), 7 ml/l (H2), and 8 ml/l (H3). The second factor is NPK fertilizer dosages (N) in 4 different treatment levels that consist of 24 g/plant (N1), 32 g/plant (N2), 40 g/plant (N3), and 48 g/plant (N4). This study showed that combination of 6 ml/l Hormonik PGR and 40 g/plant of NPK fertilizer provide the highest number of fruits per plant by 49.0 and the weight of fruit per plant by 1,572.3 g. Keywords : Concentration of Hormonik PGR, Dose of NPK Fertilizer, Production, Tomato.